Collaborative leadership: organisational structure and institutional investment to multiply innovative educational efforts among trainees. Issue 1 (1st September 2020) - Do, Albert; Li, Luming; Heller, Danielle R; Abou Ziki, Maen D; Glaser, Daniel H; Kumar, Sumit P; Huot, Stephen J
Abstract : Background: Trainees comprise a substantial employee population worldwide and there is increasing perspective of leadership as a foundational skill of physician development. In the USA, the Accreditation Council for Graduate Medical Education mandates a 'Resident/Fellow Forum' to facilitate cross-institutional engagement and communication with the Graduate Medical Education Committee. Interventions: To increase effectiveness, we conceived a 'Senate' in place of a forum, incorporating broader housestaff representation and partnerships with faculty and hospital executive leadership. The 'Yale-New Haven Hospital Resident and Fellow Senate' was supported by hospital financial resources and faculty mentorship. It provided leadership development, enhanced interdepartmental, connected multiple medical specialties, and improved housestaff engagement with institutional leaders. The Senate comprised an elected Executive Board and five councils in areas of common interest with appointed Chairs and members at large. Conclusions: We summarise the Senate's conception, structure, election process, lessons learnt and associated impact. We conclude that the creation of an institutionally supported Senate with interest-specific councils and faculty mentorship leads to qualitatively positive downstream effects on housestaff social interactions, institutional engagement and leadership opportunities.